Co-Morbidities in Children with Cerebral Palsy Undergoing Early Spine Fusion for Scoliosis - Sitoula, Prakash; Miller, Freeman (Journal of Nobel Medical College, 2014)
Introduction: Children with Cerebral Palsy (CP) may have multisystem involvement the occurrence of which increases with severity of involvement. Scoliosis is also found to be more prevalent in severely involved children with CP. Aims: This study aimed to describe co-morbidities in children with CP undergoing early spine fusion for scoliosis. Methods: A retrospective review of patients with CP Scoliosis between 1989 and 206 who were <10 years at spine fusion was done. Demographics, mental status, pre-operative weight and height and body-mass index (BMI), curve characteristics, geographic pattern of involvement and GMFCS level were reported. Co-morbidities were broadly categorized as those involving central nervous system, gastrointestinal system and respiratory system. Results: 42 patients (24 male and 18 female) with mean age of 8.1 ±1.6 years at surgery were identified. The mean preoperative weight, height, and BMI were 22 ±6.8 kilograms, 115 ±11.8 centimeters and 16 ±3.7 respectively. All patients were mentally retarded and quadriplegic. GMFCS level was V in 40 patients and IV in 2 patients. The mean Cobb angle was 83.4° ±18.3° and pelvic tilt was 18° ±10°. Seizure disorder and GER were present in 98% and 69% of patients respectively. 88% patients had gastrostomy-tube for feeding. 31% patients were tracheostomized; 46% of them were ventilator dependent. Asthma/ reactive airway disease, restrictive lung disease and obstructive respiratory disease/ sleep apnea were present in 29%, 17% and 5% of patients respectively. 19% patients had recurrent aspiration pneumonitis. Conclusion: Our study showed that children with CP Scoliosis progressing to surgical range before 10 years of age are severely involved with co-morbidities encompassing multiple organsystems. DOI: http://dx.doi.org/10.3126/jonmc.v3i1.10049 Journal of Nobel Medical College Vol.3(1) 2014; 22-26